Construction of extended adoption Model of CRM systems at the healthcare organizational level in Malaysian private hospitals - Rababah, Khalid Ali; Mohd, Haslina; Ibrahim, Huda; Mohamed Din, Aniza (2010)
Customer Relationship Management (CRM) System is very important to enhance healthcare services, improve cost-effectiveness, and accessibility of the healthcare.Therefore, study of the adoption of the CRM in healthcare at organizational level is necessary to identify factors that influence the CRM adoption.Hence, this study aims at proposing an extended adoption model of CRM systems in Malaysian private hospitals. Finding from previous studies show that the adoption factors may be influenced by innovation, organizational, and environmental factors to the perception, adoption, and implementation of CRM system. The theoretical foundations of the model is based on Innovation Diffusion Theory (IDT) and Model of Information System Innovation (ISI). Survey and interview techniques were utilized to validate the proposed extended adoption model of CRM systems. The data collected were analyzed using Structural Equation Model(SEM).The model is beneficial to the healthcare at organizational level for the short and long term planning associating the adoption of CRM in organizations.